EFEITO DE ADUBAÃ‡Ã•ES DO SUBSTRATO E FOLIAR NA FORMAÃ‡ÃƒO DE MUDAS DE CACAU (ð˜›ð˜©ð˜¦ð˜°ð˜£ð˜³ð˜°ð˜®ð˜¢ ð˜¤ð˜¢ð˜¤ð˜¢ð˜° L.) - Fasiaben, M. C. Ramos; Costa, J. Dias; DemÃ©trio, C. G. Borges; Coral, F. Joaquim (REVISTA DE AGRICULTURA, 2020)
EFEITO DE ADUBAÃ‡Ã•ES DO SUBSTRATO E FOLIAR NA FORMAÃ‡ÃƒO DE MUDAS DE CACAU (ð˜›ð˜©ð˜¦ð˜°ð˜£ð˜³ð˜°ð˜®ð˜¢ ð˜¤ð˜¢ð˜¤ð˜¢ð˜° L.)